Towards the Façades of the Future: A New Sustainability Assessment Approach. (June 2019) - Gilani, G; Pons, O; de la Fuente, A
Abstract: While the majority of the recent studies report on sustainability assessment of buildings as a whole, research on the sustainable performance of building independent elements (e.g., envelope and façades) is scarce. Façades, as the first line of defense against the undesirable external impact, may contribute to the building sustainability by reducing the amount of energy consumption and providing thermal comfort for the inhabitants, thus minimizing the environmental impact on both the building and on the environment. Despite the significance of this issue, there are a few studies that focus on sustainability assessment of façades that consider economic, environmental and social aspects; however, these aspects are generally taken into account in a decoupled manner and, often, not objectively measured. In this respect, a set of criteria and indicators for assessing sustainability of residential façade systems is presented and discussed in detail herein. In addition, a new model for assessing objectively sustainability of building façades is also presented. This approach has been obtained by using MIVES, a Multi-Criteria Decision Making model that integrates the main sustainability requirements (economic, environmental and social) and includes the concept of value functions.